2014
DOI: 10.31686/ijier.vol2.iss8.221
|View full text |Cite
|
Sign up to set email alerts
|

Ιnsider Views of CLIL in Primary Education

Abstract: The present study attempted a comparative exploration of EFL teachers’ views in relation to integrating the CLIL (Content and Language Integrated Learning) approach in the context of Greek and Cypriot primary education. It is considered that the provision of curriculum content in a second/foreign language (L2/FL) can be advantageous in terms of enhancing both subject knowledge and target language competence, and improving motivation for learning. In total, 248 Greek and 100 Cypriot Teachers of primary educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, although the students expressed positive attitudes towards the CLIL project, they also reported encountering difficulties in general and content-specific vocabulary. Griva and Kasvikis's (2015) study suggested that the Greek students in the examined contexts developed vocabulary and knowledge in the subject of History, increased their cultural awareness and appreciation of the Greek culture, enhanced cognitive and communicative skills, and improved their EFL skills. Students' willingness and positive attitude towards learning content through a L2 were also noted.…”
Section: Primary Educationmentioning
confidence: 90%
See 2 more Smart Citations
“…However, although the students expressed positive attitudes towards the CLIL project, they also reported encountering difficulties in general and content-specific vocabulary. Griva and Kasvikis's (2015) study suggested that the Greek students in the examined contexts developed vocabulary and knowledge in the subject of History, increased their cultural awareness and appreciation of the Greek culture, enhanced cognitive and communicative skills, and improved their EFL skills. Students' willingness and positive attitude towards learning content through a L2 were also noted.…”
Section: Primary Educationmentioning
confidence: 90%
“…Cypriot EFL teachers to explore teachers' views and experiences of CLIL. Griva et al (2014) found that Greek EFL teachers with a Master's degree were more likely to be familiar with CLIL and more willing to implement CLIL. Although the majority of the Greek participants agreed on possible benefits and advantages for CLIL students' learning, nearly half of them opposed CLIL implementation in the fifth and sixth grades and lower secondary education.…”
Section: Primary and Secondary Educationmentioning
confidence: 95%
See 1 more Smart Citation
“…Research into CLIL in Greek EFL education for young learners suggests its impact on cognitive and socio-emotional skills. Griva and Kasvikis (2014) cite a project that revolves around the teaching of Geography, History, and Culture by means of meeting different cultures and the use of the target language. The project is deemed to be efficient as learners developed both content knowledge and language skills.…”
Section: Clil Education and Its Added Valuementioning
confidence: 99%
“…A study on Greek and Cypriot teachers in regards to aspects of skill necessitated for CLIL teaching reports that difficulty in designing and using appropriate materials, e.g. collect material and task-design, was on vast majority agreement compared to other components such as knowing learners' need and content-competence (Griva, Chostelidou, and Panteli, 2014). Yet, in reality, material selection in CLIL teaching is prone to change, either lenient to teachers' preference (depends on teachers' ability) or students' need.…”
Section: Contentious Debates Do We Really Need Esp?mentioning
confidence: 99%